2020
DOI: 10.1108/emjb-10-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of store-attributes on food and grocery shopping behavior: insights from an emerging market context

Abstract: PurposeIn recent years, while the food and grocery retail in developed markets like Western Europe seem to be slowly facing saturation, it has been steadily growing in the Asia–Pacific region markets like India. This is mainly due to the emergence of modern retail and the changing consumer dynamics. This study purposes to assesses whether food and grocery (F&G) shoppers in India are strongly influenced by store-attributes.Design/methodology/approachDescriptive research design, a cross-sectional survey invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It also seems that providing samples of sweet fresh fruits for consumers to taste may motivate consumers to buy fruits. This is particularly true because most purchase decision-making is made at the place of purchase (Nair and Shams, 2020). Shoppers with high ratings on the VSF scale were less likely to shop for fresh fruits at club stores [1% (P < 0:05)].…”
Section: Dependent Variablementioning
confidence: 99%
“…It also seems that providing samples of sweet fresh fruits for consumers to taste may motivate consumers to buy fruits. This is particularly true because most purchase decision-making is made at the place of purchase (Nair and Shams, 2020). Shoppers with high ratings on the VSF scale were less likely to shop for fresh fruits at club stores [1% (P < 0:05)].…”
Section: Dependent Variablementioning
confidence: 99%
“…The model was confirmed, and the results showed how green marketing and personal factors influence the green food purchasing behavior in a direct and indirect way, in presence of the mediating variables' attitude toward green food and intention to buy green food. Nair and Shams [34] examined whether food and grocery (F&G) shoppers in India are strongly influenced by store-attributes. The findings show that store-attributes-atmosphere, promotion, convenience, facilities, merchandise, store personnel interaction, and services affect store choice decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings were validated by Anggraini et al (2020). In contrast, scholars (Park, 2018;Kim et al, 2020;Singh et al, 2020) suggested that bettereducated individuals strongly believed in the PED and did not show much difference than compared to least-educated consumers, whereas Ahmed et al (2007) and Nair and Shams (2020) failed to show any difference between consumers based on their age, gender, education, occupation and experience.…”
Section: Literature Reviewmentioning
confidence: 89%